The Impact of Perceived Organizational Support: The Moderating Role of Personality Traits - Alden Nelson; Kenny Kenny; Agustinus Setyawan (Dinasti Publisher, 2025)
An employee's attitude and behavior are significantly influenced by their experience working for a company. Employees will feel stressed in some situations and need to come up with ways to deal with the tension they will encounter. The purpose of this research is to know how perceived organizational support influence work meaningfulness, work engagement, and perceived stress, moderated by personality traits. In this research, primary data and secondary data are used, the primary data used is by distributing questionnaires to students who are already working. The research would be tested using the PLS-SEM program and the SPSS program to process data from the questionnaire. The study found that work engagement negatively influences perceived stress, with personality traits moderating this relationship. Personality traits also directly reduce perceived stress. Perceived organizational support (POS) positively influences perceived stress, work engagement, and work meaningfulness. Additionally, POS indirectly reduces stress through the mediating roles of work engagement, work meaningfulness, and their combination. Work meaningfulness enhances work engagement and, in turn, contributes to lowering stress. Furthermore, POS improves work engagement through the mediating effect of work meaningfulness. These findings highlight the importance of POS, meaningful work, and personality traits in fostering engagement and reducing stress in the workplace.